HEALTH, A SINE QUA NON CONDITION OF SPORTS PERFORMANCE (University Arena, 2025)
In the context of the alarming increase in the number of sports accidents with serious consequences, namely permanent or temporary inability to play, infirmity or death, the present scientific approach aims at highlighting the primordial role of health, which is - in our opinion – a sine qua non condition of sports performance, as well as some aspects of the legal liability of athlete, of the coach and of the doctor of national or Olympic team in situations where they fail to comply with their obligations under the legal provisions on working and rest time, periodic rest periods (daily and weekly), athletic leave, medical leave, health and safety at work, accidents at work, control and medical assistance, World Anti-Doping Code and International Standards, biochemical assistance, health insurance, etc.The paper aims to analyze the main categories of rights and obligations that ensure the protection of the health of athletes, and at the same time wishes to be an alarm signal in the prevention of sports accidents or athletes' deaths as a result of their activity.